Pulse electrochemical deposition and photocorrosion of copper indium diselenide thin film - Ghamarian, Nima (2012)
Copper indium diselenide (CuInSe2) because of its features such as suitable band gap value, positive flat band potential and good chemical stability made it a promising energy conversion material in photo-electrochemical cell. In this work, polycrystalline thin film of CuInSe2 (CIS) was prepared by pulse electrodeposition on clean activated ITO glass substrates from aqueous solution containing CuSO4, In2(SO4)3 and SeO2. During pulse electrodeposition duty cycles of 33- 90% were applied for fifteen minutes (total on time) to produce different surface morphologies. The probable potential for deposition was predetermined from cyclic voltammogram (CV). The deposited film was annealed at 400 oC under nitrogen gas flow to provide neutral atmosphere to improve the crystalline structure and remove excess deposited selenium. The crystalline structure of the thin film was determined from X-ray diffraction which confirmed that the deposited CIS had a tetragonal chalcopyrite structure. The CIS phase is consistent for samples deposited for all duty cycles. The optical property of thin film was determined base on the measurement by using UV-Vis spectrophotometer. The direct band gap of the deposited CIS thin film is around 1.21 eV. Thus, the electrodeposited CIS thin film is a potential candidate to be used in solar cell and energy conversion devices. Atomic force microscope (AFM) was employed to monitor the effect of duty cycles on the morphology of the thin film. It was revealed that with increasing duty cycle the surface morphology shifted from smooth to dendritic structure. Photo-electrochemical characterization (PEC) was performed under chopped white light in acidic redox medium. The CIS film was found to be a photosensitive material and showed p and n-p type semiconductoring behavior when deposited at different duty cycles. The effect of varying surface morphology on photocorrosion behavior of CIS was studied in acidic and alkaline electrolytes. Polarization curves were acquired in selected corrosive electrolytes which contained 0.5 M KCl + H2SO4 as the acidic media and 0.5 M KCl + NaOH as the alkaline media. The photocorrosion rates were evaluated from the electrochemical polarization data. The photocorrosion rates for different morphologies were estimated from current density (icorr) extracted from Tafel plots for all pH range. Finally activity and passivity behavior of the thin films were determined by interpreting the values from polarization curve peaks (Ecorr) and the rate of photocorrosion. The photocorrosion behavior of deposited CIS thin film was found to be affected by the surface morphology, photoactivity and pH of medium. The deposited thin film displayed an outstanding stability with corrosion rate of 0.122 mm per year in alkaline media for sample deposited with duty cycle 90% (the least corroded morphology) and 11.96 mm per year in acidic media for duty cycle 33% ( the most corroded morphology).